Stem Cells in Neuroendocrinology - Pfaff, Donald; Christen, Yves (Research and Perspectives in Endocrine Interactions, 2016)
This volume starts with an elementary introduction covering stem cell methodologies used to produce specific types of neurons, possibilities for their therapeutic use, and warnings of technical problems. In addition the authors report successes in achieving the derivation of a specific type of neuron. The dopamine neuron offers an important example and is discussed in more detail. Additional chapters cover problems obviously approachable with cells derived from stem cells, including their need in surgeries for pituitary cancers. The last chapter provides an overview of this particular field of research and presents a vision for its future directions. .